2019
DOI: 10.1155/2019/9042542
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Periodontal and Systemic Immune Response of Overweight Rodents to Periodontal Infection

Abstract: This study aimed to explore periodontal and systemic immune response of overweight hosts to periodontitis. Forty C57 BL/6J male mice were divided into high (HF) or low fat (LF) diet groups and fed with the two diets, respectively, for 8 weeks. Each diet group was then divided into periodontitis (P) or control (C) groups (n = 10 per group) for 10-day ligation or sham-ligation. Overweight-related parameters including body weight were measured. Alveolar bone loss (ABL) was morphometrically analyzed and periodonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Although ABL and periodontal osteoclast numbers were not affected by diet regardless of ligation or sham-ligation, leukocyte and macrophage numbers and protein levels of tumor necrosis factor α (TNF-α) in the periodontium and serum interleukin (IL)-6 levels were downregulated in periodontitis mice fed a high-fat diet. These findings indicated that an impaired immune response occurred both periodically and systemically in pre-obesity overweight mice [87]. They also evaluated the effects of obesity on macrophage infiltration and activation in periodontal tissue with periodontitis.…”
Section: Diabetes and Obesity Model Mice With Ligature-induced Periodontitismentioning
confidence: 93%
“…Although ABL and periodontal osteoclast numbers were not affected by diet regardless of ligation or sham-ligation, leukocyte and macrophage numbers and protein levels of tumor necrosis factor α (TNF-α) in the periodontium and serum interleukin (IL)-6 levels were downregulated in periodontitis mice fed a high-fat diet. These findings indicated that an impaired immune response occurred both periodically and systemically in pre-obesity overweight mice [87]. They also evaluated the effects of obesity on macrophage infiltration and activation in periodontal tissue with periodontitis.…”
Section: Diabetes and Obesity Model Mice With Ligature-induced Periodontitismentioning
confidence: 93%
“…TNF‐α can positively self‐regulate its synthesis in adipose tissue and other tissues/fluids . Moreover, a continuous increase of TNF‐α in oral fluids, triggered by obesity, would contribute to the development or worsening of inflammatory conditions such as periodontal disease, a hypothesis supported by experimental and clinical studies . TNF‐α acts through the activation of nuclear factor‐kB (NF‐kB), a transcription factor responsible for the regulation of genes associated with inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…66 Moreover, a continuous increase of TNF-in oral fluids, triggered by obesity, would contribute to the development or worsening of inflammatory conditions such as periodontal disease, a hypothesis supported by experimental and clinical studies. 19,67 TNF-acts through the activation of nuclear factor-kB (NF-kB), a transcription factor responsible for the regulation of genes associated with inflammation. 9 The production or activity of TNF-is associated with some adipokines, such as leptin, adiponectin, vaspin, and omentin, which may regulate TNF-production through NF-kB activation.…”
Section: F I G U R E 4 Meta-analysis Graphs Showing the Difference Ofmentioning
confidence: 99%
“…The most relevant linker is systemic inflammation and impaired immune response by which obesity might trigger aberrant periodontal inflammation and exacerbated alveolar bone loss [8]. Through test carried out on laboratory mice with induced obesity researchers explore significant decrease of alveolar bone level and increase of periodontal osteoclast, leukocyte, and macrophage number in obese mice with periodontitis compared with normal weight mice with induced periodontitis [16]. In periodontal tissues of monosodium glutamate-induced obesity rats activation of oxidative stress and nitrosative stress alteration and depolymerization of main connective tissues biopolymers were detected compared with rats without obesity [1].…”
Section: Introductionmentioning
confidence: 99%